The main etiological reasons of fatal type 2 myocardial infarction. (11th May 2021) - Leonova, I; Oblavatsky, D; Boldueva, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Purpose: the assessment of the proportion of myocardial infarction (MI) type 2 in the structure of mortality in a multidisciplinary hospital Material and methods. A retrospective study was made of 1, 574 autopsy protocols carried out in a multidisciplinary hospital in the period from 01.01.10 to 31.12.16, of which a group with postmortem type II MI was identified. The control group was composed of persons who died from proven atherothrombotic type 1 MI Results. In 360 cases (22.87%), the cause of death was MI. Of these, 137 cases were due to type 2 MI. The ratio of men and women was the same. Type 2 MI more often developed in elderly (48.2%) and senile (34.3%) ages; the average age of patients with type 2 MI was 71.7 ± years (68.2 ± 3 years among men and 75.3 ± 4 years among women p <0.05), which did not differ from the group with fatal type 1 MI. The main causes of death in type 2 MI were tachysystolic arrhythmias - 59.12% of cases, severe hypoxia of any etiology - 35.04%. The absence of significant stenoses of coronary artery (CA) is significantly more common in type 2 MI, and multivessel disease - in type 1 MI. In the group of patients with type 1 MI, 67.29% had multivessel lesions (Table 1). When comparing mortality in different departments of a multidisciplinary hospital, it turned out that only 29.2% of patients with type 2 MI were initially hospitalized in the cardiology department; 45.3% of patients - therapeutic, 25.5% of patients – surgical. Conclusion. Nearly one in four patients die as a result of MI, with more than 1/3 of fatal MIs occurring in type 2 MI. The main reasons for the development of type 2 MI: tachysystolic arrhythmias - 59.12%, hypoxia of various origins - 35.04%, sepsis - 2.2%. 25% of fatal type 2 MIs occurred in surgical patients.